2021
DOI: 10.1038/s41598-021-84450-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes of antibiotic prescribing pattern and its resistance to E. Coli in South Korea: a 12-year retrospective observational study

Abstract: In the present study, we investigated the pattern of changes in antibiotic prescription and antimicrobial resistance (AMR) in Escherichia coli in South Korea between 2007 and 2018. We collected data related to antibiotic prescription and AMR in E. coli from the national surveillance system. We used the Mann–Kendall test and Spearman’s correlation to identify the trends of antibiotic prescription and AMR in E. coli and to examine the relationship between them, respectively. Although we noted a significant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Furthermore, LTCFs provide post-acute care hospitalization for patients with complicated illnesses, and they play a pivotal role in the spread of CRE within healthcare systems [ 10 ]. Most vulnerable patients in LTCFs have an increased risk of acquiring infections and colonizing CRE because of their multiple underlying diseases and medications [ 11 ]. Therefore, surveillance within LTCFs and across all healthcare systems is warranted to identify the risk factors for CRE infection and to measure the impact of the CRE epidemic trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, LTCFs provide post-acute care hospitalization for patients with complicated illnesses, and they play a pivotal role in the spread of CRE within healthcare systems [ 10 ]. Most vulnerable patients in LTCFs have an increased risk of acquiring infections and colonizing CRE because of their multiple underlying diseases and medications [ 11 ]. Therefore, surveillance within LTCFs and across all healthcare systems is warranted to identify the risk factors for CRE infection and to measure the impact of the CRE epidemic trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term care facilities (LTCFs), which provide post-acute care hospitalization for patients with complicated illnesses, play a pivotal role in the spread of CRE within healthcare systems [ 10 ]. Between 2007 and 2018 in Korea, the antimicrobial resistance in LTCFs was higher than that in the general population [ 11 ]. This might be because most inpatients in LTCFs have multiple underlying diseases and are prescribed a variety of medications (including antibiotics), which makes them vulnerable to colonizing resistant organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al reported a susceptibility of 68.0% to cefotaxime in E. coli , and 33.1% of ESBL-producing strains were cultured from community-onset UTIs in 2017 [ 16 ]. Another study showed that in LTCFs, the resistance rate of E. coli to cefotaxime gradually increased, reaching 70% in 2018 [ 17 ]. When considering our results in conjunction with those of previous studies, it becomes apparent that the resistance rate and proportion of ESBL-producing strains in LTCFs are higher than those in the general population, and this trend is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of several ARGs were found from the ancient layers of the Canadian high Arctic permafrost 14 . Anthropogenic activities, particularly the overuse and misuse of antibiotics in agriculture, human medicine, and animal husbandry, have accelerated the enrichment and dissemination of ARGs [15][16][17][18] . As emerging contaminants, ARGs have been globally detected in a diversity of environmental compartments, including water, soil, and air [19][20][21][22][23][24][25][26][27] .…”
Section: Background and Summarymentioning
confidence: 99%